Multiparameter Single Cell Profiling of Airway Inflammatory Cells - Yao, Yi; Welp, Tobias; Liu, Qing; Niu, Naiqian; Wang, Xiaomei; Britto, Clemente J.; Krishnaswamy, Smita; Chupp, Geoffrey L.; Montgomery, Ruth R. (Cytometry. Part B, Clinical cytometry, 2017)
Airway diseases affect over 7% of the U.S. population and millions of patients worldwide. Asthmatic patients have wide variation in clinical severity with different clinical and physiologic manifestations of disease that may be driven by distinct biologic mechanisms. Further, the immunologic underpinnings of this complex trait disease are heterogeneous and treatment success depends on defining subgroups of asthmatics. Because of the limited availability and number of cells from the lung, the active site, in‐depth investigation has been challenging. Recent advances in technology support transcriptional analysis of cells from induced sputum. Flow cytometry studies have described cells present in the sputum but a detailed analysis of these subsets is lacking. Mass cytometry or CyTOF (Cytometry by Time‐Of‐Flight) offers tremendous opportunities for multiparameter single cell analysis. Experiments can now allow detection of up to ∼40 markers to facilitate unprecedented multidimensional cellular analyses. Here we demonstrate the use of CyTOF on primary airway samples obtained from well‐characterized patients with asthma and cystic fibrosis. Using this technology, we quantify cellular frequency and functional status of defined cell subsets. Our studies provide a blueprint to define the heterogeneity among subjects and underscore the power of this single cell method to characterize airway immune status. © 2016 International Clinical Cytometry Society